A fabrication and characterization of luffa/PANI/PEO biocomposite nanofibers by means of electrospinning - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2022)
Purpose This paper aims to address the production of biocomposite nanofibers using luffa natural fibers and polyaniline conductive polymer/polyethylene oxides (PANI/PEO). Design/methodology/approach In this study, luffa natural fibers are extracted by chemical method. After mixing the treated luffa (TL) with the PANI/PEO solution, TL/PANI/PEO nanofibers were produced by electrospinning (ES) method under different ES parameters to examine the optimal conditions for nanofiber production. Then TL/PANI/PEO biocomposite nanofibers prepared in different weight ratios were produced to analyze the effects of luffa in the morphology and thermal properties of the biocomposite nanofibers. The characterization analysis of TL/PANI/PEO biocomposite nanofibers was performed by scanning electron microscopy, Fourier transform infrared spectroscopy (FTIR) and differential scanning calorimetry (DSC) analysis methods. Findings The analysis shows that different weight ratios of TL to PANI/PEO changed the morphology of the membrane. When increasing the weight ratio of TL, the morphological structure of TL/PANI/PEO transformed from nanofiber structure to thin film structure. The appearance of O-H peaks in the FTIR results proved the existence of TL in PANI/PEO nanofibers (membrane). Moreover, an increase in the weight ratio of luffa from 2% to 7.5% leads to an increase in the peak intensity of the O-H group. Regarding DSC analysis, biocomposite nanofibers improved the thermal properties. According to all results, 2%wt TL/PANI/PEO showed optimal morphological properties. Originality/value Plant cellulose was extracted from the luffa, one of the natural fibers, by method of alkali treatment. A new type of biocomposite nanofibers was produced using TL blend with PANI via electrospinning method.
Keywords: Polymers; Electrospinning; Polyaniline; Nanofibers; Biocomposite; Luffa; Natural fibers; CELLULOSE-ACETATE NANOFIBERS; LUFFA-CYLINDRICA; MECHANICAL-PROPERTIES; ELECTRICAL-PROPERTIES; NATURAL FIBER; FLAX-FIBER; COMPOSITES; BEHAVIOR; SENSOR